Obesity, Diabetes, Coffee, Tea, and Cannabis Use Alter Risk for Alcohol-Related Cirrhosis in 2 Large Cohorts of High-Risk Drinkers. (31st January 2021) - Whitfield, John B.; Masson, Steven; Liangpunsakul, Suthat; Mueller, Sebastian; Aithal, Guruprasad P.; Eyer, Florian; Gleeson, Dermot; Thompson, Andrew; Stickel, Felix; Soyka, Michael; Muellhaupt, Beat; Daly, Ann K.; et al.
Abstract : INTRODUCTION: Sustained high alcohol intake is necessary but not sufficient to produce alcohol-related cirrhosis. Identification of risk factors, apart from lifetime alcohol exposure, would assist in discovery of mechanisms and prediction of risk. METHODS: We conducted a multicenter case-control study (GenomALC) comparing 1, 293 cases (with alcohol-related cirrhosis, 75.6% male) and 754 controls (with equivalent alcohol exposure but no evidence of liver disease, 73.6% male). Information confirming or excluding cirrhosis, and on alcohol intake and other potential risk factors, was obtained from clinical records and by interview. Case-control differences in risk factors discovered in the GenomALC participants were validated using similar data from 407 cases and 6, 573 controls from UK Biobank. RESULTS: The GenomALC case and control groups reported similar lifetime alcohol intake (1, 374 vs 1, 412 kg). Cases had a higher prevalence of diabetes (20.5% (262/1, 288) vs 6.5% (48/734), P = 2.27 × 10 −18 ) and higher premorbid body mass index (26.37 ± 0.16 kg/m 2 ) than controls (24.44 ± 0.18 kg/m 2, P = 5.77 × 10 −15 ). Controls were significantly more likely to have been wine drinkers, coffee drinkers, smokers, and cannabis users than cases. Cases reported a higher proportion of parents who died of liver disease than controls (odds ratio 2.25 95% confidence interval 1.55–3.26). Data from UK Biobank confirmed these findings for diabetes, body mass index, proportion of alcohol as wine, and coffee consumption. DISCUSSION: If these relationships are causal, measures such as weight loss, intensive treatment of diabetes or prediabetic states, and coffee consumption should reduce the risk of alcohol-related cirrhosis.